Health services and territorial hierarchies in Brazil - Evangelina Oliveira (European Regional Science Association (ERSA), 2001)
This paper deals with the different territorial hierarchies established by the consumption of health services in Brazil. Flows are classified in two groups, one for general services (general hospitals, laboratory analysis and dental services), another for specialised, higher level attention (specialist consultations and exams, major surgery organ transplants). Urban centers are classified in terms of the level of equipment they are endowed with. The traditional approach to analysis of polarisation in terms of dominant flows between centers has been extended by Rabino to deal with other types of flows, such as counter-hierarchical and transversal flows (see Rabino and Occelli, 1997, and Berroir et al., 2001). The research reported here shows that in Rio Grande do Sul, a southern State selected for a preliminary analysis, the two networks identified illustrate the different types of organization. The higher level services networks is strongly hierarchical, with well defined, nested levels. The general services network, on the other hand, is far less dependent on the hierarchy of the centres, exhibiting, as expected, both transversal and shorter distance flows.
Keywords: 330